2021
DOI: 10.3390/ph14050482
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Novel Inhibitors of α-Glucosidase: An Application of Quantitative Structure Activity Relationship and Structure-Based Virtual Screening

Abstract: α-Glucosidase is considered a prime drug target for Diabetes Mellitus and its inhibitors are used to delay carbohydrate digestion for the treatment of diabetes mellitus. With the aim to design α-glucosidase inhibitors with novel chemical scaffolds, three folds ligand and structure based virtual screening was applied. Initially linear quantitative structure activity relationship (QSAR) model was developed by a molecular operating environment (MOE) using a training set of thirty-two known inhibitors, which showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…It should be noted, most α-glucosidase inhibitors which are available today as diabetes medicine, can also inhibit α-amylase, and therefore specific α-glucosidase inhibitors are probably more tolerable 8 . On the other hand, the potent and safe α-glucosidase inhibitors can be useful in the treatment of obesity and other α-glucosidase related diseases 9 11 .
Figure 1 Schematic diagram illustrating the mechanism of action of α-amylase and α-glucosidase (ChemDraw 18.2).
…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, most α-glucosidase inhibitors which are available today as diabetes medicine, can also inhibit α-amylase, and therefore specific α-glucosidase inhibitors are probably more tolerable 8 . On the other hand, the potent and safe α-glucosidase inhibitors can be useful in the treatment of obesity and other α-glucosidase related diseases 9 11 .
Figure 1 Schematic diagram illustrating the mechanism of action of α-amylase and α-glucosidase (ChemDraw 18.2).
…”
Section: Introductionmentioning
confidence: 99%
“…from a virtual screening study; however these molecules have not been tested for α-amylase activity. Halim et al 18 have reported a virtual screening study using a subset of ZINC database coupled with QSAR study as an rational approach to identify α-glucosidase inhibitors; the molecules have been screening against S. cerevisiae α-glucosidase.…”
mentioning
confidence: 99%
“…The substrate molecule (isomaltose) cocrystallized in the isomaltase 3D structure was manually docked in the a-glucosidase by aligning the protein sequence and structure, and the RMSD of the protein structure and sequence alignment was reported. 23 To validate the docking protocols, the redocking was performed using the substrate molecule with the α-glucosidase active site residues. The superimposed RMSD of the reported substrate and the redocked substrate was calculated in angstrom (Å).…”
Section: Methodsmentioning
confidence: 99%